COVID-19 made it harder to access period products: The effects of a pandemic on period poverty - Hunter, Emily; Palovick, Kirstin; Teni, Mintesnot T.; Sebert Kuhlmann, Anne (Frontiers in Reproductive Health, 2022)
Background Prior to the COVID-19 pandemic, a few studies started to highlight the extent of period poverty in the U.S., especially among low-income women and girls. Preliminary data documenting the effects of the pandemic, subsequent economic downturn, and closure of schools and businesses on menstrual hygiene management are now emerging. Objective This study explores the relationship between the effects of the COVID-19 pandemic and period poverty among a nationally representative sample of U.S. adults. Methods Cross-sectional, secondary analyses of a 2021 nationwide, self-administered, online panel survey used weighted logistic regressions to assess the relationship between the COVID-19 pandemic making it more difficult to access products and missing work due to a lack of products. Responses from 1037 menstruating individuals age 18-49 were included. Results Overall, 30% of the sample indicated the COVID-19 pandemic made it more difficult to access period products, 29% struggled to purchase period products in the past year, and 18% missed work due to a lack of period products. Those who identified as Hispanic (aOR 2.06 95%CI 1.29-3.29) and had children under 18 (aOR 15.3 95%CI 1.03-2.26) were more likely to indicate that the pandemic made it harder to access period products. Subsequently, those who indicated that the pandemic made it more difficult to access period supplies were more likely to report missing work due to a lack of period products in the past 12 months (aOR 4.32 95%CI 4.69-6.94). Discussion The COVID-19 pandemic exacerbated period poverty, especially among those in the U.S. who struggle with accessibility and affordability of products. Future pandemic response planning should consider period products as a basic need for vulnerable households. In addition, policies that increase the affordability and accessibility of period products for all should help reduce menstruation-related absenteeism from work.